Tidal volume according to the 4-point sealing forces of a bag-valve-mask: an adult respiratory arrest simulator-based prospective, descriptive study - Uhm, Dongchoon (BMC Emerg Med, 2021)
BACKGROUND: For adequate ventilation during bag-valve-mask ventilation, rescuers should ensure a proper mask seal using the one-handed or two-handed technique. Little is known about the magnitude of sealing forces of a bag-valve-mask needed for adequate ventilation. This study aimed to explore the effect of the 4-point sealing forces of a bag-valve-mask on tidal volume while using the one-handed technique, focusing on the moderating effect of C length (the distance from the thumb to the index finger in the C shape of the one-hand EC grip). METHODS: A prospective, descriptive simulation study was conducted. A convenience sample of 125 undergraduate paramedic students from two universities was recruited. A self-reported questionnaire was used to collect subjective variables. Tidal volumes, 4-point sealing forces of the mask, peak pressure, and C length of the C shape in the one-hand EC grip were measured using the mechanical lung model under a simulated adult respiratory arrest. Hierarchical regression analysis was used to determine the moderating effect of C length on tidal volume in bag-valve-mask ventilation. RESULTS: The average C length, peak pressure, and tidal volume were 7.54 (± 1.85) cm, 11.62 (± 5.40) cmH(2)O, and 321.66 (± 135.18) mL, respectively. The average range of the 4-point sealing forces was 0.03–0.69 N. The apex sealing force was the weakest among the 4-point sealing forces. Hierarchical regression analysis demonstrated that tidal volume accounted for 62.7% of the variance by C length, peak pressure, and apex sealing force during bag-valve-mask ventilation (F = 9.676, p < 0.001). C length moderated the effect of the apex sealing force and peak pressure on the tidal volume, meaning the higher the peak pressure and apex sealing force, the more the tidal volume and the longer the C length. CONCLUSION: This first simulation study measuring the 4-point sealing forces during bag-valve-mask ventilation provides effective advice that can be adopted in clinical practice without side effects and underpins the importance of continuous retraining and assessment focused on individual physical characteristics, such as C length and bag-valve-mask sealing forces.